Linguistic risk-taking in inclusive contexts: The case of Developmental Language Disorder (DLD) - Schick, Kim-Sarah; Rohde, Andreas (Cahiers de l’ILOB / OLBI Journal, 2025)
A Linguistic Risk-Taking Passport is an excellent means to orchestrate Task-Based Language Teaching (TBLT) and different learner needs in inclusive settings. We identified core areas in which learners with Developmental Language Disorder (DLD) face linguistic risk-taking. Two semi-structured expert interviews were conducted and qualitative content analysis was carried out to identify specific linguistic risks of learners with DLD in and outside of school.Our results suggest that learners with DLD need systematic support in choosing and facing the next appropriate linguistic risks that lead to healthy risk-taking. We argue that this can contribute to an exploitation of their learning potential and to social-emotional well-being. Numerous linguistic risks are related to an increased sensitivity in the affective domain. The data analysis led to tentative hypotheses for a Linguistic Risk-Taking Passport for learners with DLD.